1996
DOI: 10.1128/iai.64.11.4488-4494.1996
|View full text |Cite
|
Sign up to set email alerts
|

CD14-mediated signal pathway of Porphyromonas gingivalis lipopolysaccharide in human gingival fibroblasts

Abstract: Lipopolysaccharide (LPS) induces expression of inflammatory cytokines in monocytes/macrophages via CD14, one of the LPS receptors, which is expressed predominantly in these cells. It has been demonstrated thatPorphyromonas gingivalis LPS (P-LPS) also is able to induce inflammatory cytokines in human gingival fibroblasts. Therefore, it is important to determine whether CD14 is expressed in gingival fibroblasts and to define the P-LPS-mediated signal-transducing mechanism in the cells. In this study, we observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…The evidences for the expression of CD14 in human gingival fibroblasts are controversial. Some reports demonstrated that CD14 is expressed in human gingival fibroblasts (25)(26)(27), whereas other reports found that human gingival fibroblasts fail to express CD14 (23,45). Sugawara et al (24) showed that human gingival fibroblasts consist of populations that are heterogeneous on the basis of different levels of mCD14 expression, and that this explains the possible reasons for the heterogeneous expression of mCD14 in human gingival fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidences for the expression of CD14 in human gingival fibroblasts are controversial. Some reports demonstrated that CD14 is expressed in human gingival fibroblasts (25)(26)(27), whereas other reports found that human gingival fibroblasts fail to express CD14 (23,45). Sugawara et al (24) showed that human gingival fibroblasts consist of populations that are heterogeneous on the basis of different levels of mCD14 expression, and that this explains the possible reasons for the heterogeneous expression of mCD14 in human gingival fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…MyD88, an adapter molecule for the TLR/interleukin-1 receptor family, is also essential for the cellular responsiveness to the bacterial cell surface components such as lipopolysaccharide (21). Human gingival fibroblasts constitutively express CD14 (22)(23)(24)(25)(26), TLR4 (27,28) and MyD88 (28), and these molecules therefore may mediate cytokine production in lipopolysaccharidestimulated human gingival fibroblasts. Actually, the findings of recent studies have demonstrated that CD14 (22)(23)(24)(25)(26) and TLR4 (27,28) mediated production of inflammatory cytokines in response to lipopolysaccharide from Porphyromonas gingivalis in human gingival fibroblasts.…”
mentioning
confidence: 99%
“…Since there is no clear evidence that endothelial cells are able to express CD14 receptor on their membrane surfaces and that some CD14-expressing cells were not immunoreactive to OX-42, fibroblasts are likely to be another cell type that express the LPS receptor within the subarachnoid space. It is interesting that fibroblasts has previously been shown to display high levels of CD14 and this event was shown to mediate the LPS-induced stimulation of AP-1 transcription factor (39).…”
Section: Dual-labeling Datamentioning
confidence: 99%
“…Currently, the ability of human gingival fibroblast on CD14 expression remains controversial. Several studies reported that human gingival fibroblast could express mCD14 and the LPS-induced signal-transducing pathway was mediated by this LPS receptor (7). In contrast, Hayashi et al (52) found that neither mCD14 peptides nor CD14 message was expressed by human gingival fibroblast, but human gingival fibroblast could be activated by LPS and sCD14.…”
Section: Discussionmentioning
confidence: 98%
“…Recent data showed that human gingival fibroblast could express membrane-bound CD14 (mCD14), which mediated the LPS-induced signaltransducing pathway, leading to the production of cytokines (7). Wang et al (24) even demonstrated that mCD14 could be constitutively expressed by fibroblasts derived from gingival connective tissues but not those from other connective tissues.…”
mentioning
confidence: 99%